The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11596-015-1403-8
|View full text |Cite
|
Sign up to set email alerts
|

The trends in maternal mortality between 1996 and 2009 in Guizhou, China: Ethnic differences and associated factors

Abstract: China bears a large burden of global maternal mortality, and the largest burden of maternal deaths in China is in poor western provinces. This study aimed to investigate the trends in maternal mortality and its associated factors in Guizhou province of western China between 1996 and 2009, and examine differences between minority and non-minority counties. A population-based, longitudinal, retrospective study was performed in a poor western province of China with a considerably large ethnic minority population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The increased per GDP was associated with decreased MMR and explained the most MMR declining trend. Other provinces of China studies also found this association [ 13 , 23 ]. Economic environment was also significantly associated with other low and middle-income countries, but little related to developed countries [ 24 ].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The increased per GDP was associated with decreased MMR and explained the most MMR declining trend. Other provinces of China studies also found this association [ 13 , 23 ]. Economic environment was also significantly associated with other low and middle-income countries, but little related to developed countries [ 24 ].…”
Section: Discussionmentioning
confidence: 52%
“…As a key finding that higher level of hospital delivery rate and antenatal care rate were associated with a lower level MMR, the previous alone clarified the most contrast in MMR between minority and non-minority counties and county variance. Increased hospital delivery rate being associated with decreased MMR has been evidenced by other studies in China [ 13 , 16 ]. Hospital delivery with skilled attendants may decrease the risk of maternal death.…”
Section: Discussionmentioning
confidence: 60%
“…China bears some burden of global maternal mortality, the largest part being in the poor western provinces 19 . Hospital delivery should be completely covered because it has been recognized as an effective strategy in reducing maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our survey, only 10.8% of ethnic minority women had received five or more antenatal visits, 13.5% gave birth in hospital, and 1.7% had a caesarean section. Equally low levels of uptake of maternity care have been reported previously for ethnic minority women living across Western China [15, 34–36]. The extremely low caesarean section rates are particularly worrying: while caesarean section rates cannot be a substitute for the measurement of levels of maternal mortality, research has found that the caesarean section rate is negatively associated with maternal mortality when under 10% [37], and rates below 5% suggest an unmet need for life saving surgery [38].…”
Section: Discussionmentioning
confidence: 86%